INFLUENCE OF FERTILIZER TYPES AND RATES ON THE GROWTH AND FRUIT YIELD OF THREE CUCUMBER (Cucumis sativus L.) VARIETIES - IWALEWA, E. A.; AMUJOYEGBE, B. J. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2019)
Since its introduction into the rainforest agroecology, cucumber production is reportedly very low partly owing to inadequate agronomic management practices especially fertilizer application. Experiment on the effects of different fertilizer applications on growth and fruit yield of three varieties of cucumber was carried out at the Teaching and Research Farm, Obafemi Awolowo University, Ile-Ife, Nigeria. The experiment was a 4×3×3 factorial experiment laid out using a randomized complete block design in three replications. The treatments include four nitrogen fertilizer sources (Organic fertilizer, Liquid fertilizer, Urea fertilizer and NPK fertilizer) applied at the rates of 0, 75 and 120 kg N/ha on three varieties of cucumber (Poinsett 78, Marketer and Marketmore). Data were collected on growth parameters, phenology and fruit yield components. The longest vine was recorded due to the application of 120 kg N/ha of NPK on Poinsett variety. While Poinsett had the highest vegetative growth, Marketmore had the highest number of fruit and fruit yield per hectare. There was interaction between the effect of variety and fertilizer type on vine length, vine diameter, number of leaves, dry matter accumulation, total chlorophyll content, number of days to flowering and fruit length. It could be concluded that application of 120kg N/ha of inorganic nitrogen fertilizer promotes the growth and yield of cucumber. Poinsett performed best as regards vegetative growth compared to others and with respect to fruit yield, Marketmore performed best compared to the other two.